Modeling hydrological processes and analyzing water balance utilizing remote sensing data and physical hydrological models in the Songnen Plain, China - Zhong Lu; Jinliang Zhang; Chaoqun Li; Xi Wang; Guoping Lei; Kuo Li (PLoS ONE, 2025)
Climate change and human activities have a substantial effect on the regional water cycle. An accurate simulation of the water cycle process in the Songnen Plain under the influence of climate change and human activities can aid in gaining a comprehensive understanding of the regional water cycle change pattern in a changing environment, which has significant scientific and practical value. Based on the MIKE SHE/MIKE 11 model, this study utilizes multi-source remote sensing data, measured hydrological data, and other basic data as data sources to simulate the water cycle process in the Songnen Plain over the past 40 years and analyze its pattern of change. The results show that groundwater level data derived from GRACE and GLDAS exhibits great accuracy in topographically varied regions and low accuracy in proximity to rivers. The estimated groundwater data and measured runoff data, integrated with the MIKE SHE/MIKE11 model, accurately replicate the changes in the water cycle within the Songnen Plain. Over the years, the Songnen Plain has experienced an average actual evapotranspiration of 421.61 mm, with an average rate of change of −0.36 mm/a. The average surface runoff has been 36.26 mm, with an average rate of change of −0.025 mm/a. The average groundwater level is 169.2 m, indicating a weak downward trend. The variations in the water balance of the Songnen Plain surplus and deficit throughout different time periods were 0.804 billion m³, 0.098 billion m³, −1.15 billion m³, and 0.645 billion m³, respectively. Regarding alterations in various land uses, water supply and demand are most pronounced in arid regions, where the water balance exhibits a trend of initial decline followed by an increase; paddy fields experienced a water deficit across different time periods, with the severity of the deficit intensifying; the water balance deficit of building land increases with economic growth; and the water balance of other land uses was contingent upon climatic conditions. This study provides novel ideas and methods for regional simulation of water cycle processes in regional water scarcity literature by innovatively integrating GRACE and GLDAS data with the MIKE SHE/MIKE 11 model.